Unraveling Authority of Coal Mining Management by the Regional Government and Its Implications for Regional Autonomy - Bakung, Dolot Alhasni (Indonesian Journal of Advocacy and Legal Services, 2020)
The region has the authority to manage and regulate its territory independently based on the mandate of Article 18 paragraph (2) of the 1945 Constitution. One such authority is to manage natural resources in this case conducting coal mining. The management of coal mining under the Minerba Act places the district/city government in authority in its management. Meanwhile, the Local Government Law places the provincial government also in possession of this management authority. This gave birth to the dualism of regulation in terms of the authority to manage coal, giving rise to a contradiction between one rule and another. The problem in this study is First, how is the condition of coal mining management by local governments in the perspective of regional autonomy? Second, what are the implications of the current coal mining arrangements by the regional government? The results of the study showed that coal mining authority from the district/municipal government under the Minerba Act then was transferred to the provincial government based on the Regional Government Law was reasonable because of various problems that arose from the authority of the district/city government. However, this fact puts the authority of coal mining management in dualism and disharmony in its regulation. This dualism has implications for the disruption of the pattern of authority relations between the central and regional governments, financial management between the central and regional governments, and the division of supervisory authorities between the central and regional governments.